2015
DOI: 10.5604/12314005.1137914
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Concentration of Magnetic Particles on Ferrooil’s Dynamic Viscosity as a Function of Temperature and Shear Rate

Abstract: Ferrooil's dynamic viscosity changes significantly alter the tribological properties and thus its usefulness as a lubricant of the sliding journal bearings. Due to the fact that the ferrooil demonstrate strong magnetic polarity in the presence of an external magnetic field, it is possible to control the viscosity by means of an external magnetic field just by changing the intensity as well as by changing of the concentration of magnetic particles. There is presented an effect of the changes of the concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In previous works, presented by the author of many publications, among others, in [2,5,6], there have been carried out the experimental studies of effect of concentration of the magnetic particles on the properties of ferro-oil viscosity both the presence or absence of an external magnetic ISSN: 1231-4005 e-ISSN: 2354-0133 DOI: 10.5604/12314005.1213575 field, in the aspect of changes in the basic operating parameters of bearing: i.e. temperature, pressure and shear rate η = η (T, p, θ).…”
Section: The Theoretical Foundationsmentioning
confidence: 99%
“…In previous works, presented by the author of many publications, among others, in [2,5,6], there have been carried out the experimental studies of effect of concentration of the magnetic particles on the properties of ferro-oil viscosity both the presence or absence of an external magnetic ISSN: 1231-4005 e-ISSN: 2354-0133 DOI: 10.5604/12314005.1213575 field, in the aspect of changes in the basic operating parameters of bearing: i.e. temperature, pressure and shear rate η = η (T, p, θ).…”
Section: The Theoretical Foundationsmentioning
confidence: 99%
“…A special cup and a thermostatic system were used to maintain a constant temperature of the sample, which was (80.0 ± 0.2)°C. The volume fraction of magnetic particles in the tested oil was 6% (in the papers [1,2] can be found information on an impact of the concentration of magnetic particles in the oil on its viscosity). The measurements could be carried out to a shear rate of about 10 5 [1/s] (above this value, the maximum allowable torque on the rheometer rotor detector was exceeded for this sample at mentioned conditions).…”
Section: Fig 1 Fitting Of Curves Described By the Considered Relatimentioning
confidence: 99%
“…The study of ferro-viscosity oils with different concentrations of magnetic particles in the presence of a constant external magnetic field of variable intensity so far conducted by the authors, the results of which can be found, inter alia, in [1,2], leads to certain conclusions. First of all:…”
Section: The Theoretical Foundationsmentioning
confidence: 99%
“…with increasing the concentration of magnetic particles in the ferro-oil also increases the value of the dynamic viscosity; it has been observed [1] than 7-fold increase between the extreme concentrations, i.e. under consideration: 1% and 8% for a dependence on constant temperature, viscosity increases are not proportional to increases in the magnetic particles concentrations [1], which may indicate that the viscosity is not merely a derivative of the increased molecular weight of the mixture, but also results from the other properties of its internal structure, such as magnetic particles coagulation in the oil especially at higher concentrations, the presence of a constant external magnetic field affects additional increases the dynamic viscosity of ferro-oil [2], observed increases range from several percent at low concentrations to nearly 50% at the highest [2], the largest increase in viscosity is accompanied by switching the magnetic fields, i.e., the change between 0 and 50 mT, and regardless of the concentration is approximately 10-15% of the initial value [2], the further increasing the value of magnetic induction of external magnetic field results in minor increments the viscosity values up to stabilize at around 200 mT [2]. Also, research conducted this year by the authors [3] indicate that the values of the magnetic induction of 150-200 mT follows to overall directional arrangement of magnetic particles in ferrooil (full magnetic saturation), responsible for the increase in its viscosity.…”
Section: The Theoretical Foundationsmentioning
confidence: 99%